(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
This scientific article aims to propose an established infrastructure of a LoRaWAN technology network in the city of Mosul as an initial starting point for this pioneering technology in the field of wireless communication and IoT technologies and then suggests advertising the proposed model to all cities of Iraq as a national project aimed at developing the capabilities of wireless communications in the field of IoT technologies based on what is known as Low Power Wide Area Networks (LPWA). This article deals with the high capabilities and distinguished characteristics provided by this technology and how to employ and construct, with a study of the scientific and research value as well as the economic feasibility, and calculations of the total expected costs of the construction and installation of this model in the city of Mosul in order to cover both sides of the town and also, to study the possibility and effectiveness of covering the geographical area of wireless broadcasting, and concludes with the most essential recommendations. In addition, a reference supplement to the websites of the most important international institutions and companies that have introduced this technology within their production and industrial solutions has been included.